KUALITAS MAKANAN, KUALITAS PELAYANAN DAN PERSEPSI HARGA TERHADAP MINAT PEMBELIAN ULANG PADA RUMAH MAKAN CIGANEA PURWAKARTA - Ella Laela (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
This research was conducted to find out what factors can influence consumers in re-buying interest. In this study used three independent variables of Food Quality (X1), Service Quality (X2), and Price Perception (X3) while Purchase Interests Repeat (Y) as the dependent variable. After reviewing the literature and formulating hypotheses, data collection was carried out by distributing questionnaires to 97 consumers at Ciganea - Purwakarta Restaurant who had made an exclusive purchase using non probility sampling techniques. For analysis and elaboration of data using SPSS version 21. Then there are several tests performed in analyzing data, such as measuring instruments, classical assumption tests, multiple linear regression analysis and hypothesis testing. Based on the results of the analysis found that the three independent variables have a significant and positive effect on the dependent variable. Food Quality Variables have a positive effect of 0.785 with a significance level of 0,000. Service Quality Variables have a positive effect of 0.633 with a significance level of 0.000. Price Perception Variables have a positive effect of 0.734 with a significance level of 0.000. Adjusted R Square of the four variables is 0.680 or 68% which means that the three variables are able to explain the variation in the dependent variable of 68.0 percent with 32.0 percent explained by other variables not used in this study.